Influence of the Temperature Changes on Stresses in Carbon Composite Fastening Bolts - Angelika Arkuszyńska; Jan Godzimirski; Marek Rośkowicz (Technologia i Automatyzacja Montażu)
High joint strength of composite structures can be achieved by using mechanical fasteners. The materials used for rivets and bolts havelower coefficients of thermal expansion than composites in the direction perpendicular to the reinforcement fibers. It is suspected, therefore, that temperature changes can cause stress changes in mechanical fasteners. The purpose of this study was to experimentally determine and analytically substantiate the values of stress changes resulting from a change in temperature in the range from -20 to 60C in M8 steel bolts fastening carbon composite. The value of stress changes was estimated to be around 100 MPa, which can consequently lead to joint unsealing or plastic deformation of the mechanical fastener.